Bad Apple : Merits of Mischief #1 - Burns, T. R., 1978- (New York : Aladdin, 2012)
After accidentally killing a substitute teacher with an apple, twelve-year-old Seamus Hinkle is sent to Kilter Academy where, in order to excel as he always has, he must behave badly and pull pranks on his teachers, but along with new friends Lemon and Elinor he discovers that there is more to the Academy than meets the eye.
Ages 8-12.
Keywords: Behavior -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Tricks -- Fiction; JUVENILE FICTION / Social Issues / New Experience; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Humorous Stories; Human behavior -- Fiction; Private schools -- Fiction; Tricks -- Fiction; School stories; Humorous fiction; Humorous fiction